2023
DOI: 10.3847/1538-4357/acc177
|View full text |Cite
|
Sign up to set email alerts
|

Joint Modelling of Dust Scattering and Thermal Emission: The Spider Complex

Abstract: Observations across the electromagnetic spectrum of radiative processes involving interstellar dust—emission, absorption, and scattering—are used to constrain the parameters of dust models and more directly to aid in foreground removal of dust for extragalactic and cosmological observations. Dust models can benefit from more independent constraints from complementary observations. Here, we quantify the relationship between scattered light and thermal emission from dust in a diffuse (cirrus) intermediate-latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…A comparison with Panel (c) shows that strong similarity exists between the submillimeter dust map and the optical data. This reinforces our assumption that the same dust population emits thermally in the submillimeter and scatters the starlight in the optical (as expected by dust models, Zhang et al 2023; and see discussion in Section 8.2). This correlation is also supported by observations in various other studies (e.g., Ienaka et al 2013;Miville-Deschênes et al 2016;Román et al 2020;Marchuk et al 2021;Lim et al 2022;Smirnov et al 2023).…”
Section: Dust Priors: a Better Path For Background Modeling?supporting
confidence: 87%
See 3 more Smart Citations
“…A comparison with Panel (c) shows that strong similarity exists between the submillimeter dust map and the optical data. This reinforces our assumption that the same dust population emits thermally in the submillimeter and scatters the starlight in the optical (as expected by dust models, Zhang et al 2023; and see discussion in Section 8.2). This correlation is also supported by observations in various other studies (e.g., Ienaka et al 2013;Miville-Deschênes et al 2016;Román et al 2020;Marchuk et al 2021;Lim et al 2022;Smirnov et al 2023).…”
Section: Dust Priors: a Better Path For Background Modeling?supporting
confidence: 87%
“…The central region of the Spider field was previously observed by Dragonfly in 2014 and 2017, with earlier configurations of the array (Zhang et al 2023). In Zhang et al (2023), the Dragonfly Spider data is investigated jointly with Herschel data to test dust and scattering models.…”
Section: Field 1: the Spider Field (Extreme Cirrus Emission)mentioning
confidence: 91%
See 2 more Smart Citations
“…Sandage (1976) identified the nature of these faint optical diffuse cloud structures, which are called integrated flux nebulae (IFN) because they are illuminated not by the light of a single star but by the ISRF of the Galaxy. Zhang et al (2023) demonstrated the benefits of joint modeling of the intensity of scattered light and thermal emission from dust, focusing for illustration on an optically thin IFN and infrared cirrus called the Spider.…”
Section: Introductionmentioning
confidence: 99%